A quantitative assay to study the lipid selectivity of membrane-associated systems using solution NMR. Issue 78 (2nd September 2020) - Medina-Carmona, Encarnacion; Varela, Lorena; Hendry, Alex C.; Thompson, Gary S.; White, Lisa J.; Boles, Jessica E.; Hiscock, Jennifer R.; Ortega-Roldan, Jose L.
Abstract : We present a simple methodology to assess the phospholipid selectivity of membrane-associated compounds in natural membranes. Abstract : The activity of membrane proteins and compounds that interact with the membrane is modulated by the surrounding lipid composition. However, there are no simple methods that determine the composition of these annular phospholipids in eukaryotic systems. Herein, we describe a simple methodology that enables the identification and quantification of the lipid composition around membrane-associated compounds using SMA-nanodiscs and routine 1 H– 31 P NMR.